Predicting radio frequency radiation from mobile communication base stations - Ismail, Ahmad Fadzil; Sidek, Nurul Izzah; Abdullah, Khaizuran; Hashim, Wahidah (International Association of Computer Science and Information Technology Press, 2013)
While the spectrum growth is expected to increase exponentially in the future years to come, the imminent query would be as whether the current spectrum management process is capable of fulfilling all future requirements. Public interest in the potential health issues relating to cellular or mobile communication base station (BS) and other radio communication facilities emphasize the importance of having an accessible and easy to understand information on electromagnetic (EM) and radio frequency radiation (RFR) levels in the surrounding environment. The information is considered critical in order to assess the potential radiation level prior and during the roll-out of planned or future services such as the 4G, Terrestrial Trunked Radio (TETRA), Worldwide Interoperability for Microwave Access (WiMax), Local Multipoint Distribution Service (LMDS) and others. The paper outlines the attempts of developing a specialized software tool that can gauge the RFR concentration within a particular area. The tool encompasses; among many, the capability of facilitating as well as ensuring that the RFR monitoring activities and planning can be carried out efficiently and effectively.